View Hint | View Answer | Workspace | Discuss In Forum | Report
? = 10 x 5 ÷ 3 - 2 + 3
As per question
= 10 ÷ 5 + 3 x 2 - 3
Apply the rule BODMAS
B -Brackets first
O -Orders (i.e. Powers and Square Roots, etc.)
DM -Division and Multiplication (left-to-right)
AS -Addition and Subtraction (left-to-right)
? = 10 x 5 ÷ 3 - 2 + 3
= 10 ÷ 5 + 3 x 2 - 3
Apply the rule BODMAS
Do things in Brackets First
(Powers, Roots) before Multiply, Divide, Add or Subtract.
Multiply or Divide before you Add or Subtract
= 10 ÷ 5 + 3 x 2 - 3
= 2 + 3 x 2 - 3
Addition
= 2 + 6 - 3
Subtraction
= 8 - 3 = 5
View Hint | View Answer | Workspace | Discuss In Forum | Report
Given expression, (50 x 2) W (28 T 4)
After interchanging the letters with symbols, we get
(50 ÷ 2) + (28 x 4)
Given expression, (50 x 2) W (28 T 4)
After interchanging the letters with symbols, we get
(50 ÷ 2) + (28 x 4) = 25 + 112 = 137
View Hint | View Answer | Workspace | Discuss In Forum | Report
Given, 40* 2* 4 * 3 * 8
Let us check all the options one by one.
From option (a), putting the signs in given equation, we get
40 + 2 - 4 ÷ 3
= 8 ⇒ 42 - 4/3 = 8
⇒ 126 - 4 = 24 ⇒ 122 = 24
∴ L H S ≠ R H S
So, option (a) is incorrect.
From option (b), putting the signs in given equation, we get
40 ÷ 2 + 4 = 3 x 8
⇒ 20 + 4 = 24 ⇒ 24 = 24
Given, 40* 2* 4 * 3 * 8
Let us check all the options one by one.
From option (a), putting the signs in given equation, we get
40 + 2 - 4 ÷ 3
= 8 ⇒ 42 - 4/3 = 8
⇒ 126 - 4 = 24 ⇒ 122 = 24
∴ L H S ≠ R H S
So, option (a) is incorrect.
From option (b), putting the signs in given equation, we get
40 ÷ 2 + 4 = 3 x 8
⇒ 20 + 4 = 24 ⇒ 24 = 24
LHS = RHS
Hence, option (b) is correct and there is no need to check remaining options.
In each of the following questions, all the equations except one have been solved according to a certain rule. You are required to solve the unsolved equation following the same rule and to choose the correct answer out of the given options.
View Hint | View Answer | Workspace | Discuss In Forum | Report
As, 4 - 4 ⇒ 4 x 4 + 1 = 17
6 - 6 ⇒ 6 x 6 + 1 = 37
As, 4 - 4 ⇒ 4 x 4 + 1 = 17
6 - 6 ⇒ 6 x 6 + 1 = 37
2 - 2 ⇒ 2 x 2 + 1 = 5
Similarly, 5 - 5 ⇒ 5 x 5 + 1 = 26
∴ ? = 26
View Hint | View Answer | Workspace | Discuss In Forum | Report
After replacing the sign according to question
1 P 45 R 2 Q 2 S 4
= 1 + 45 ÷ 2 x 2 - 4
After replacing the sign according to question
1 P 45 R 2 Q 2 S 4
Apply the BODMAS Rule
= 1 + 45 ÷ 2 x 2 - 4
= 1 + 22.5 x 2 - 4
= 1 + 45 - 4 = 42